Analysis of Product Innovation and Pricing in Increasing Competitiveness and Sales: A Case Study of Gado-Gado Suramadu MSMEs - Nur Arisah; Ika Wisudawaty (Citakonsultindo, 2025)
This research is motivated by the importance of product innovation and pricing strategy as two key elements in maintaining the sustainability and increasing the competitiveness of MSMEs, particularly in the traditional culinary sector. The purpose of this study is to analyze how product innovation implemented by the Gado-Gado Suramadu MSME, along with a pricing strategy determined based on quality and production costs, contributes to increased sales. This study uses a qualitative approach with data collection techniques through in-depth interviews, direct observation, and literature review. Data are analyzed thematically by identifying patterns from field results and linking them to relevant theories. The results show that product innovation, such as adding topping variations and traditional presentations, provides added value that has a positive impact on customer satisfaction and loyalty. Meanwhile, a pricing strategy that takes production costs and consumer purchasing power into account creates a balance between quality and selling value, and maintains the financial stability of the business. In conclusion, the synergy between product innovation and pricing strategy plays a significant role in increasing the competitiveness and sales revenue of the Gado-Gado Suramadu MSME. This research is expected to be a practical reference for MSME actors in developing relevant business strategies, as well as being a consideration for policy makers in designing MSME coaching and development programs in the culinary sector